Three-dimensional scaffolds for enhanced tissue regeneration - Tam, Chong Meng (2009)
An emerging area of interest in tissue engineering is to fabricate biomimetic constructs that closely resembles the extracellular matrix architecture, so as to allow cells to undergo minimum remodeling as tissue regenerates in vivo. The fibrous and porous structure of electrospun scaffolds makes them ideal candidates for tissue engineering applications. By having control over the porosity and architecture of scaffolds potentially allows control over the cell migration rate into the scaffold, as well as the cellular functional and gene expression changes. However, the degree of control of these parameters is still at infancy stage. Researchers have produced scaffolds using electrospinning which resultantly end up in two-dimensional membrane structures, often lacking the porosity and depth essential for cell proliferation during tissue regeneration.